Characterization of the CpG island methylator phenotype subclass in papillary thyroid carcinoma - Gu, Pengfei; Zeng, Yu; Ma, Weike; Zhang, Wei; Liu, Yu; Guo, Fengli; Ruan, Xianhui; Chi, Jiadong; Zheng, Xiangqian; Gao, Ming (Frontiers in Endocrinology, 2022)
CpG island methylator phenotype (CIMP), characterized by the concurrent and widespread hypermethylation of a cluster of CpGs, has been reported to play an important role in carcinogenesis. Limited studies have explored the role of CIMP in papillary thyroid carcinomas (PTCs). Here, in genome-wide DNA methylation analysis of 350 primary PTCs from TCGA database that were assessed using the Illumina HumanMethylation450K platform, our study helps to identify two subtypes displayed markedly distinct DNA methylation levels, termed CIMP (high levels of DNA methylation) and nCIMP subgroup (low levels of DNA methylation). Interestingly, PTCs with CIMP tend to have a higher degree of malignancy, since this subtype was tightly associated with older age, advanced pathological stage, and lymph node metastasis (all P < 0.05). Differential methylation analysis showed a broad methylation gain in CIMP and subsequent GGST analysis based on the significantly methylated probes in CIMP showed remarkable enrichment in epithelial mesenchymal transition and angiogenesis hallmark pathways, confirming that the CIMP phenotype may promote the tumour progression from another perspective. Analysis of tumour microenvironment showed that CIMP PTCs are in an immune-depletion status, which may affect the effectiveness of immunotherapy. Genetically, the significantly higher tumour mutation burden, higher copy number alteration both in genome and focal level, confirming the genomic heterogeneity and chromosomal instability of CIMP. Corresponding to the above findings, PTC patients with CIMP showed remarkable poor clinical outcome as compared to nCIMP regarding OS and PFS. More importantly, CIMP was associated with worse survival independent of known prognostic factors.